Three-dimensional dislocation dynamics analysis of size effects on void growth. (15th January 2015) - Chang, Hyung-Jun; Segurado, Javier; LLorca, Javier
Abstract : Plastic void growth in face-centered cubic single crystals subjected to hydrostatic tension was studied by means of three-dimensional dislocation dynamics. The simulations showed the development of a size effect on the void growth rate of the type "the larger, the faster". It was found that plastic void growth by dislocation shearing of the voids was inhibited for submicron void sizes due to the lack of active dislocation sources near to the void surface.